1990
DOI: 10.1128/aac.34.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the diagnosis, treatment, and prevention of Pneumocystis carinii pneumonia

Abstract: In summary, recent advances in our ability to diagnose, treat, and prevent recurrences of pneumocystis pneumonia have significantly improved the clinical management of this infection, especially in HIV-1-infected individuals. As current investigations allow our therapeutic armamentarium in this disease to be strengthened even further, it is likely that pneumocystis pneumonia will pose a diminishing threat to those patients currently most susceptible to this infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
3

Year Published

1991
1991
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 45 publications
1
26
0
3
Order By: Relevance
“…Initial studies of Diff-Quik-stained scid mouse lung homogenates revealed stained bodies with morphologies and sizes comparable to previously published observations describing P. carinii in rat and human samples (see Masur et al, 1989;Davey & Masur, 1990;Smulian & Walzer, 1992). That the scid mice bred by us were indeed positive for P. carinii was confirmed by the demonstration that bodies of the size and morphology of P. carinii were present in Giemsa-stained histological lung sections (not presented).…”
Section: Validation Of Cyst Enumeration Methodssupporting
confidence: 58%
See 3 more Smart Citations
“…Initial studies of Diff-Quik-stained scid mouse lung homogenates revealed stained bodies with morphologies and sizes comparable to previously published observations describing P. carinii in rat and human samples (see Masur et al, 1989;Davey & Masur, 1990;Smulian & Walzer, 1992). That the scid mice bred by us were indeed positive for P. carinii was confirmed by the demonstration that bodies of the size and morphology of P. carinii were present in Giemsa-stained histological lung sections (not presented).…”
Section: Validation Of Cyst Enumeration Methodssupporting
confidence: 58%
“…That the scid mice bred by us were indeed positive for P. carinii was confirmed by the demonstration that bodies of the size and morphology of P. carinii were present in Giemsa-stained histological lung sections (not presented). Furthermore, as presented below, animals treated with trimethoprim/sulphamethoxazole, an agent known to be effective against P. carinii (see Masur et al, 1989;Davey & Masur, 1990;Smulian & Walzer, 1992), did not contain such bodies.…”
Section: Validation Of Cyst Enumeration Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the standard agents for treatment, pentamidine and a combination of trimethoprim and sulfamethoxazole (TMP-SMZ), have high response rates, they often produce severe side effects which necessitate cessation of therapy in more than 60% of AIDS patients (5). Better-tolerated modes of treatment are needed.…”
mentioning
confidence: 99%